1981
DOI: 10.1161/01.res.48.3.386
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hemorrhagic hypotension on urinary kallikrein excretion, renin activity, and renal cortical blood flow in the pig.

Abstract: SUMMARY We measured urinary kallikrein by its esterolytic and kinin-forming activity in 5-minute urine samples obtained throughout continuous bleeding experiments in pigs to correlate possible changes in urinary kallikrein excretion during hemorrhagic hypotension with renin activity and renal cortical blood flow. Renin activity was determined in venous blood samples and renal cortical blood flow was estimated by the radiolabeled microsphere technique. The rate of urinary kallikrein excretion was increased abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
(37 reference statements)
1
12
0
Order By: Relevance
“…However, it is possible that this particular effect is mediated by binding to a different All receptor or to the high affinity binding sites for AIII, which are less effectively occupied by saralasin (Devynck & Meyer, 1978). The fact that the peak in kallikrein excretion precedes that of PRA, as seen previously (Maier et al, 1981;, indicates that such a mechanism is also unlikely.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, it is possible that this particular effect is mediated by binding to a different All receptor or to the high affinity binding sites for AIII, which are less effectively occupied by saralasin (Devynck & Meyer, 1978). The fact that the peak in kallikrein excretion precedes that of PRA, as seen previously (Maier et al, 1981;, indicates that such a mechanism is also unlikely.…”
Section: Discussionmentioning
confidence: 80%
“…The vasoconstricting RAS is, therefore, in several ways linked to the vasodilator kallikrein-kinin-system and it has even been suggested that these two vasoactive systems might be regulated simultaneously (Misumi et al, 1983). In our previous studies on haemorrhagic hypotension in pigs we found increased excretion of urinary kallikrein within the arterial pressure range of 100 to 70 mm Hg, which corresponded to the relative maintenance of renal cortical blood flow (RCBF) and glomerular filtration rate (GFR) (Maier et al, 1981). Since the increase in kallikrein excretion during haemorrhagic hypotension was always accompanied by increased plasma renin activity, it is possible that the observed kallikrein increase was a consequence of elevated endogenous All induced by haemorrhage.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The increase in fetal plasma renin and angiotensin II concentrations after blood loss were consistent with the possibility that the renin-angiotensin system plays a role in the restoration of blood pressure in the fetus of this species also. Sharply increased renin activity was seen in the plasma of young post-natal pigs (Maier, Starlinger, Wagner, Meyer & Binder, 1981) when the reduction in their blood pressures came into the range experienced before birth (Macdonald et al , 1983.…”
Section: Effect Of Haemorrhagementioning
confidence: 97%
“…The increase in prostaglandin E2 outflow in venous renal blood after short-term normothermic ischemia [17] and the elevated urinary kallikrein excretion produced by renal hypoxia in hypovolemic pigs [18] suggest that the postischemic hyperemia following short-term normo thermic ischemia may at least in part be induced by kal likrein and/or prostaglandins. Kallikrein is known to have a twofold action: by way of kinin formation it has a vasodilating effect on the smooth muscle cells of the ves sels walls, and it activates prostaglandin synthesized in the kidneys, which in turn may induce vasodilatation [19].…”
mentioning
confidence: 99%